2007
DOI: 10.1016/j.bbrc.2007.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Short-hairpin RNA-mediated stable silencing of Grb2 impairs cell growth and DNA synthesis

Abstract: Grb2 is an SH2-SH3 protein adaptor responsible for linking growth factor receptors with intracellular signaling cascades. To study the role of Grb2 in cell growth, we have generated a new COS7 cell line (COS7 shGrb2 ), based on RNAi technology, as null mutations in mammalian Grb2 genes are lethal in early development. This novel cell line continuously expresses a short hairpin RNA that targets endogenous Grb2. Stable COS7 shGrb2 cells had the shGrb2 integrated into the genomic DNA and carried on <10% of normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…WASp activation is more complex than previously believed (5,6,26,27,32). In an inactivated state, WASp exists in a closed conformation with the GBD region binding the cofilin homology domain in the carboxy terminus (14).…”
Section: Discussionmentioning
confidence: 94%
“…WASp activation is more complex than previously believed (5,6,26,27,32). In an inactivated state, WASp exists in a closed conformation with the GBD region binding the cofilin homology domain in the carboxy terminus (14).…”
Section: Discussionmentioning
confidence: 94%
“…The expression plasmid encoding the catalytically inactive form of SHP-2, SHP-2CA, was previously described (26). The Grb2 short hairpin RNA (shRNA) construct (pU6 ϩ27 -ShGrb2) directed against Grb2 nucleotides 310 to 330 (GAT GTG CAG CAC TTC AAG GTT) used for knockdown studies is as described previously (8). The strategy to generate the Grb2YF form unrecognizable by the Grb2 shRNA, the Sil-Grb2YF construct, is as described previously (8).…”
Section: Methodsmentioning
confidence: 99%
“…The Grb2 short hairpin RNA (shRNA) construct (pU6 ϩ27 -ShGrb2) directed against Grb2 nucleotides 310 to 330 (GAT GTG CAG CAC TTC AAG GTT) used for knockdown studies is as described previously (8). The strategy to generate the Grb2YF form unrecognizable by the Grb2 shRNA, the Sil-Grb2YF construct, is as described previously (8). This was achieved by incorporating seven silent mutations in the myc-Grb2YF plasmid within the region targeted by Grb2 shRNA (GAC GTC CAA CAT TTT AAA GTA; the silent mutations are underlined) (GenScript Corporation, Piscataway, NJ).…”
Section: Methodsmentioning
confidence: 99%
“…We have recently found that Fes binds PA and participates in a PLD-induced pathway of myeloid differentiation (15). PLD2 is associated with EGFR signaling by binding to Grb2 at two specific residues (Y169 and Y179) that leads to activation of the growth factor pathway (16)(17)(18). PA interacts with Sos during EGF-induced membrane recruitment and Ras activation (6).…”
mentioning
confidence: 99%